VD_FINDINFO HC / 2013 / 537 vom 15. August 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT, NOVA | 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)